Implications of building code enforcement and urban expansion on future earthquake loss in East Africa: case study—Blantyre, Malawi - Nicola Giordano; Raffaele De Risi; John Macdonald; Katsuichiro Goda; Innocent Kafodya; Ignasio Ngoma (Natural Hazards, 2023)
Rapid and uncontrolled urbanisation in many parts of Africa is a significant driver of earthquake risk. New constructions are usually built with no compliance with seismic codes, which results in a critical increase in the vulnerability of the building stock. To quantitatively assess the potential consequences of unregulated urbanisation, this study investigates the effect of building code enforcement and urban expansion on the future earthquake loss in the city of Blantyre, Malawi. The analysis, performed within a probabilistic loss assessment framework, estimates the net present value of 30-year aggregated seismic loss for different urban expansion rates and code enforcement scenarios. The results show that high urbanisation rates and lack of building regulations could lead to a threefold increase in average seismic losses in the next thirty years. On the contrary, effective code enforcement could cap the seismic loss increase at 13%, highlighting the financial gain from effective disaster risk reduction programmes.